2001
DOI: 10.1007/s005950170197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Development of Normal Foregut and Tracheoesophageal Fistula in an Adriamycin Rat Model Using Three-Dimensional Image Reconstruction

Abstract: To examine the developmental process of the normal trachea and esophagus and their maldevelopment leading to tracheoesophageal fistula (TEF), we performed three-dimensional (3-D) image reconstruction of the developing foregut in normal and adriamycin (ADM)-induced TEF rats. Microscopic images of serial sections of embryos from seven normal and 14 ADM-treated rats killed every half a day after 11-14 days' gestation were traced and reconstructed using a 3-D construction imaging system (TRI, RATOC System Engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 19 publications
(21 reference statements)
0
54
0
Order By: Relevance
“…The need for 3D visualization of events in the developing embryo has previously been recognized and addressed in a number of recent studies [17][18][19][20][21][22]. Williams et.al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The need for 3D visualization of events in the developing embryo has previously been recognized and addressed in a number of recent studies [17][18][19][20][21][22]. Williams et.al.…”
Section: Discussionmentioning
confidence: 97%
“…and Sasaki et.al. [21,22] described tracheo-oesophageal separation during embryogenesis by compiling sequential 2D images from H & E stained sections at several stages of foregut development. They clearly demonstrated the developmental events in great detail, but reconstruction from images of serial sections presents a number of technical problems.…”
Section: Discussionmentioning
confidence: 99%
“…Crisera et al [1999a] have reported that the fistula arises as the posterior branch of a tracheal trifurcation with the main bronchi, elongates caudally and fistulalises into the stomach. Splide et al [2002a] also reported a discontinuity between the fistula and the stomach, while other authors reported that the fistula developed from caudal foregut maintaining a connection with the stomach throughout Sasaki et al, 2001]. The fistula is lined with ciliated columnar respiratory epithelium from its proximal origin, transitioning into stratified squamous oesophageal epithelial lining at a variable distance caudally [Merei et al, 1997a].…”
Section: Observations Of Phenotype Of the Modelmentioning
confidence: 99%
“…In the ventral foregut mesoderm, condensed cellular patterns are associated with the outgrowth of the lung buds [Morrisey and Hogan, 2010]. Possoegel et al [1998] and others have reported disturbances in mesodermal cell pattern, describing the cellular architecture as disorganised and loosely arranged around the foregut in the ARM with loss of the circular pattern detected in control embryos at both E12 and E13 [Sasaki et al, 2001]. As well as signalling derangements discussed anon, failure of these fields to form could physically deter organogenesis; however, the detail of this mechanism is unexplained.…”
Section: Disturbances Of Cell Mechanisms In the Modelmentioning
confidence: 99%
“…In irst theory, the respiratory system develops as a result of rapid outgrowth from the original foregut tube [2], but in an alternative theory, there is active growth of a mesenchymal septum which develops in the coronal plane and, as a result, separates the foregut lumen into ventral (respiratory) and dorsal (gastrointestinal) structures [3]; however, direct evidence of septum formation has been lacking, casting doubt on this theory.…”
mentioning
confidence: 99%